Dietary sodium restriction decreases urinary NGAL in older adults with moderately elevated systolic blood pressure free from chronic kidney disease. (21st July 2020) - Wang, Wei; Chonchol, Michel; Seals, Douglas R; Nowak, Kristen L
Abstract : Increased aortic stiffness may contribute to kidney damage by transferring excessive flow pulsatility to susceptible renal microvasculature, leading to constriction or vessel loss. We previously demonstrated that 5 weeks of dietary sodium restriction (DSR) reduces large-elastic artery stiffness as well as blood pressure in healthy middle-aged/older adults with moderately elevated systolic blood pressure (SBP) who are free from chronic kidney disease (CKD). We hypothesized that DSR in this cohort would also reduce urinary concentrations of renal tubular injury biomarkers, which predict incident CKD in the general population. We performed a post hoc analysis using stored 24 hours urine samples collected in 13 participants as part of a randomized, double-blind, crossover clinical trial of DSR (low sodium (LS) target: 50 mmol/day; normal sodium (NS) target: 150 mmol/day). Participants were 61±2 (mean±SEM) years (8 M/5 F) with a baseline blood pressure of 139±2/82±2 mm Hg and an estimated glomerular filtration rate of 79±3 mL/min/1.73 m 2 . Twenty-four hour urinary sodium excretion was reduced from 149±7 to 66±8 mmol/day during week 5. Despite having preserved kidney function, participants had a 31% reduction in urinary neutrophil gelatinase-associated lipocalin concentrations with just 5 weeks of DSR (LS: 2.8±0.6 vs NS: 4.2±0.8 ng/mL, p<0.05). Results were similar when normalized to urinary creatinine (urinary creatinine did not change between conditions). Concentrations of another kidney tubular injury biomarker, kidney injury molecule-1, were below the detectable limit in all but one sample. In conclusion, DSR reduces an established clinical biomarker of kidney tubular damage in adults with moderately elevated SBP who are free from prevalent kidney disease.